Influence of crosslinker and ionic comonomer concentration on glass transition and demixing/mixing transition of copolymers poly(N-isopropylacrylamide) and poly(sodium acrylate) hydrogels - Zarzyka, Iwona (Springer Berlin Heidelberg, 2013)
Hydrogels based on N-isopropylacrylamide and sodium acrylate as ionic comonomer were synthesized by free radical polymerization in water using N,N′-methylenebisacrylamide as crosslinker and ammonium persulfate as initiator. The glass transition of dried copolymers poly(N-isopropylacrylamide) (PNIPA) and poly(sodium acrylate) (SA) gels and demixing/mixing transition of PNIPA-SA hydrogels swollen with increasing amounts of water were studied using conventional differential scanning calorimetry. In the crosslinked polymers, the glass transition linearly increases, and the transition range becomes broader, with increasing crosslinker content. Increasing content of ionic comonomer also produces an increase of glass transition temperature, which moves to higher temperatures with higher sodium acrylate fraction. The influence of chemical structure of PNIPA-SA hydrogels on the lower critical solution temperature (LCST) of PNIPA-SA/water mixtures during heating and cooling was quantified as function of the content of the crosslinker and the ionic comonomer, as well as water content of the hydrogel in the range from 95 to 70 wt%. At parity of water content, the LCST occurs at higher temperatures for gels containing higher amounts of sodium acrylate. Similarly, the introduction of N,N′-methylenebisacrylamide causes an increase of the LCST, which grows with increasing of crosslinking degree of the hydrogel.